2020
DOI: 10.1002/aocs.12376
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Physicochemical and Flavor Characteristics of Chicken Nuggets during Air Frying and Deep Frying

Abstract: Chicken nuggets were air‐fried and deep‐fried for various times at the same temperature. The moisture content, oil content, color, texture, volatile compounds, and lipids degradation of the chicken nuggets were investigated. The evolution rate of the moisture content, oil content, color, and texture were much higher during deep frying than during air frying. Air frying required more time to produce similar quality attributes as those of deep‐fried chicken nuggets. On average, the oil content of the air‐fried c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…This leads to superficial dehydration and the gradual formation of a crust on the surface of the food (Zaghi et al, 2019). Moisture loss has been reported for air-fried protein foods such as chicken nuggets and sardines (Cao et al, 2020;Ferreira et al, 2017). Cao et al (2020) found that the moisture content of chicken nuggets decreased from 140 g/100 g dry basis to 60 g/100 g dry basis after air frying for 18 min at 180 • C (356 • F).…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…This leads to superficial dehydration and the gradual formation of a crust on the surface of the food (Zaghi et al, 2019). Moisture loss has been reported for air-fried protein foods such as chicken nuggets and sardines (Cao et al, 2020;Ferreira et al, 2017). Cao et al (2020) found that the moisture content of chicken nuggets decreased from 140 g/100 g dry basis to 60 g/100 g dry basis after air frying for 18 min at 180 • C (356 • F).…”
Section: Resultsmentioning
confidence: 98%
“…This leads to superficial dehydration and the gradual formation of a crust on the surface of the food (Zaghi et al., 2019). Moisture loss has been reported for air‐fried protein foods such as chicken nuggets and sardines (Cao et al., 2020; Ferreira et al., 2017). Cao et al.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The texture of each test sample was examined at 25°C using a TA XTplus texture analyzer (Stable Micro Systems, Haslemere, England) according to the previous method (Cao et al, 2020). The adopt TAP model was used to assess the texture of potato strips and chicken drumsticks.…”
Section: Methodsmentioning
confidence: 99%